Vertical financial interest and corporate influence - Matthias Hunold; Frank Schlütter (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2019)
The established literature on partial vertical ownership has derived distinct pro- and anti-competitive effects, depending on whether the upstream or the downstream firm holds the shares (forward or backward). We show that forward ownership can have the same effects as backward ownership (and vice versa) when it entails both profit and control rights. Moreover, we demonstrate novel anti-competitive effects of partial ownership that arise when the upstream tariffs are non-linear. This contrasts well-established findings that are based on linear tariffs and adds to the current debate on how to treat partial shareholdings in merger control.
Keywords: L22; L40; L8; 330; corporate influence; financial interest; minority shareholding; partial ownership